Frequency of home visits where general practitioners are exposed to a problem different from that foreseen – a Swiss cross-sectional study (Swiss Medical Weekly, 2021)
BACKGROUND: When a home visit is considered, patients’ suspected health problems are important for correct triage, the decision  for or against the visit and allocation of the visit to a general practitioner (GP) or a nurse practitioner. Misjudgment might lead to suboptimal patient outcomes.OBJECTIVE: We aimed to evaluate the accuracy of suspected health problems (based on pre-visit assessments) by comparing them with the actual health problems (post-visit assessments) and investigating associated factors.METHODS: GPs of the Swiss Sentinel Surveillance Network (Sentinella) reported pre-visit and post-visit assessments and patient characteristics for up to 20 consecutive home visits, which they conducted in 2019. Using multivariable logistic regressions, we investigated associations between patient and clinical factors and unconfirmed suspected health problems from pre-visit assessments and unforeseen actual health problems from post-visit assessments.RESULTS: Overall, 114 GP practices participated. The GPs reported 1496 patient visits with a total of 1789 and 1762 health problems from pre-visit and post-visit assessments, respectively, that were included in the analysis. Musculoskeletal and circulatory problems were the most common in patients receiving home visits. The health problems from pre-visit and post-visit assessments were unconfirmed and unforeseen in15% and 13% of the cases, respectively. Older age (odds ratio [OR] 1.1 in 10-year steps; 95% confidence interval [95% CI] 1.0–1.3) and urgent visits (OR 1.7 compared with regular visits; 95% CI 1.1–2.6) showed a trend for more unforeseen health problems.CONCLUSION: When home visits were conducted, about one out of seven health problems from pre-visit and post-visit assessments were unconfirmed and unforeseen. Particularly when patients were older or visits were urgent, there were higher odds of unconfirmed and unforeseen health problems.These results should be considered when triaging patients.